Marjinalisasi Perempuan di Wilayah Politik - Aminah Sahal (Justicia Islamica, 2005)
This study aims to analyze the marginalization of women in the political sphere and the factors that influence it. The method used is qualitative with a descriptive-analytical approach, through a literature review and data analysis regarding the representation of women in politics. The results show that the limitations of women in politics are caused by structural factors, patriarchal culture, and policies that do not support women's participation. In addition, gender stereotypes and lack of access to political resources also reinforce this marginalization. Although various affirmative policies have been implemented, their implementation still faces various obstacles. This study emphasizes the need for more effective strategies in increasing the role of women in politics, both through political education, capacity building, and more inclusive policies. Thus, more equal participation of women in politics can be realized in a sustainable manner.